Rwanda : First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility and Request for Waiver of Performance Criteria. (IMF Staff Country Reports; Country Report ;, 2003)
This paper assesses Rwanda's First Review Under the Three-Year Arrangement Under the Poverty Reduction and Growth Facility (PRGF) and Request for Waiver of Performance Criteria. Performance under the PRGF-supported program has been encouraging. However, poverty is pervasive, and the economy, which remains heavily dependent on rain-fed agriculture and external assistance, is vulnerable to changes in climate and in international developments. The 2003 program supports critical operations envisaged under the Poverty Reduction Strategy Paper, including the transition to democracy and military demobilization.